Landed Property of Churches and Denominational Associations in Poland - Głębocki, Benicjusz (Quaestiones Geographicae, 2010)
Historical factors are presented that have determined landed property belonging to churches and denominational associations in Poland. The article then moves to post-war times to discuss the size and structure of church property resources in 1950, before its appropriation by the State in 1952, and after its restoration to the ecclesiastical owners following the systemic transformation of 1989. The form and ways of recovery of church property are discussed, as well as its present size, structure and distribution.